2011
DOI: 10.1080/10810730.2010.546489
|View full text |Cite
|
Sign up to set email alerts
|

TheLong Live KidsCampaign: Awareness of Campaign Messages

Abstract: Media interventions are one strategy used to promote physical activity, but little is known about their effectiveness with children. As part of a larger evaluation, the purpose of this study was to assess the short-term effect of a private industry sponsored media literacy campaign, Long Live Kids, aimed at children in Canada. Specifically, we investigated children's awareness of the campaign and its correlates. Using a cohort design, a national sample (N = 331, male = 171; mean age = 10.81, SD = 0.99) complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…After one year of the VERB campaign implementation, nearly 75% of tweens had unaided/aided recall of the campaign . Similarly, 60.4% of children reported unaided/aided recall of a PA communication campaign conducted among 9-12 year old children in Canada (Faulkner et al, 2011). It is noteworthy, however, that contrary to the measures used in the present study, the items assessing recall (unaided or aided) of the two latter campaigns included the name of the campaign.…”
Section: Categoriesmentioning
confidence: 72%
“…After one year of the VERB campaign implementation, nearly 75% of tweens had unaided/aided recall of the campaign . Similarly, 60.4% of children reported unaided/aided recall of a PA communication campaign conducted among 9-12 year old children in Canada (Faulkner et al, 2011). It is noteworthy, however, that contrary to the measures used in the present study, the items assessing recall (unaided or aided) of the two latter campaigns included the name of the campaign.…”
Section: Categoriesmentioning
confidence: 72%
“…Several researchers have addressed the efficacy of anti-"obesity" campaigns and their reception by target audiences (for example, Faulkner et al 2011, Lewis et al 2010, Puhl et al 2012, Walls et al 2011. Thus far, however, little academic research has been directed at the ways in which commercial research companies contribute to the decisions of government departments or agencies about health-related social marketing campaign initiatives, including those directed at "obesity" prevention and control.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, tweens' recall of the WIXX advertising campaign was not significantly associated with levels of PA, screen time, weight status, and SES (although a nearly significant association was observed for income), suggesting equitable reach of the campaign. Moreover, the likelihood of recalling the WIXX ads was significantly associated with only two PA beliefs, suggesting that the WIXX campaign did not appear to reach only those more positively predisposed toward PA. For comparison purposes, it was reported that highly active kids and those showing higher SES were more likely to recall the VERB and the LLK campaigns during the first years of these campaigns implementation (Faulkner et al, 2011;Huhman et al, 2008). Although the exact explanation of this observation remains elusive, some interesting features of the campaign might be suggested.…”
Section: Discussionmentioning
confidence: 87%
“…In the context of the VERB campaign, it was observed that the more physically active youth, white girls, and youth having higher socioeconomic status (SES) were more likely to recall the campaign during the first year of the campaign implementation . Similarly, active kids and those having higher SES were more likely to recall the Long Live Kids (LLK) campaign (Faulkner et al, 2011), suggesting that the initial reach of these two PA campaigns was not initially equally distributed into the target audience.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation